(untitled) (Research Announcements "Heritage BG", 2025)
The research is a proposal for the UNESCO list of the Palace and Botanical Garden of Balchik as a cultural landscape. It is structured following the Operational Guidelines for the Implementation of the World Heritage Convention. The research could serve as a proposal for a cultural landscape for Bulgaria, as the country does not have a single one of this type on the World Heritage List.